Role of microRNAs in neuroendocrine neoplasms of the stomach - I. N. Peregorodiev; S. V. Vinokurova; V. Yu. Bohyan; V. V. Delektorskaya; O. A. Malikhova; V. A. Gorbunova; B. I. Sakibov; D. S. Elkin; I. S. Stilidi (Успехи молекулярной онкологии)
Neuroendocrine neoplasms (NENs) are a heterogeneous group of rare epithelial tumors that arise from cells with a neuroendocrine phenotype. NENs are found in the gastrointestinal tract and pancreas – 60 % of all localities. The incidence of gastric NENs is about 9 % of all neuroendocrine tumors of the gastrointestinal tract and 0.3 % of all stomach tumors. Stomach neuroendocrine tumors (NETs) are classified into three clinico-pathological types, based on etiology, pathogenesis and morphology. There are also separate neuroendocrine cancers: small- and large-cell. The prognosis and approach to treatment of various types of gastric NENs differs significantly. Modern methods of instrumental diagnostics, immunohistochemical methods of morphological research, along with light microscopy, do not always allow us to accurately assess the malignant potential of a tumor and individualize the treatment process. One of the promising directions in the study of NETs is to determine the molecular mechanism underlying their development, in particular the role of microRNAs. This direction can open a new vector of understanding the pathogenesis, determining the prognosis of the disease, as well as finding new application points for the drug treatment of NETs. MicroRNAs are a class of short non-coding RNA molecules (18–25 nucleotides). MicroRNAs can be involved in the regulation of all major cellular processes, including proliferation and differentiation, metabolism, signaling pathways, and apoptosis. A study of microRNA expression in tissues revealed tumor-specific microRNAs. In contrast to a number of other malignant tumors, microRNA expression in patients diagnosed with NENs is poorly understood. MicroRNA-222 and microRNA-202 are among the few microRNAs that have been demonstrated in the NETs of the stomach.